Panniculitis as a rare clinical manifestation of genetically determined abnormalities of α1-antitrypsin – review of the literature - Maciejewska-Radomska, Agata; Wilkowska, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2011)
α 1-Antitrypsin (AAT) is a serine protease inhibitor responsible for regulating proteinases' activity in the blood. α 1-Antitrypsin deficiency is a result of SERPINA 1 gene mutation and it is one of the most common genetic abnormalities in Caucasians. There are over 130 different alleles for this gene. Some of them are responsible for low AAT levels in the serum, while other variants encode defective glycoproteins – functionally impaired. Patients with decreased AAT serum level are at high risk of serious pulmonary diseases (chronic pulmonary obstructive disease, asthma bronchiale, emphysema) or liver cirrhosis. On the other hand, it should be mentioned that there is a possibility of systemic life-threatening symptoms in patients with the mutated AAT gene and normal AAT levels. Panniculitis is one of the rarest manifestations of AAT deficiency. The disease is characterised by a typical clinical picture with deep, painful inflammatory infiltrations, ulcerations, fistulas and oily liquid. It may develop in a patient with a mutated gene and concomitant decreased or normal AAT level. In this article, particular attention is paid to the diagnostic aspects of SERPINA 1 gene mutations, especially in patients who have a mutated gene with a normal level of α 1-antitrypsin in the serum.